CO2 emitted from peat use in horticulture supports a lower emission factor - Bidhya Sharma; Hongxing He; Nigel T. Roulet (Carbon Management)
Peat extracted for horticulture is used for growing food, ornamental plants and for soil augmentation. Peatlands are large carbon (C) stores, and the use of extracted peat in aerobic, off-site conditions have implications on the accounting of CO2 emissions. The IPCC (2006, 2013) emission factor for peat use assumes instant oxidation i.e., all extracted peat is mineralized to CO2 in the same year. This is reasonable for peat used for fuel, but horticultural peat takes several decades to decompose. Using historical and present peat extraction data in Canada we calculate a time-integrated emission based on a first-order decomposition model of peat since 1940; when horticultural peat extraction approximately started. Our data compilation shows 36 Mt of peat C has been removed from peatlands (1994–2022) for horticultural use with extraction increasing at the rate of 10.93Kt/year. We calculate approximately 11.9 Mt CO2-C (95% CI= 10.7-12.7) has been released into the atmosphere from the decomposition of the extracted peat between 1940–2022, an estimate that is 2.8 to 3.4 times lower than what the IPCC default would suggest. Our findings have implications for comparing the impacts of peat-based growing media to other alternatives and to C taxes that could apply to horticultural peat users.